2020
DOI: 10.3390/cancers12113386
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Clinical Use of Exosomes as a Personalized Contrast Media and Theranostics

Abstract: An appropriate combination of biomarkers and imaging technologies will become standard practice in the future. Because the incidence of and mortality from cancers is rising, the further study of new approaches for the early detection and precise characterization of tumors is essential. Extracellular vesicles (EVs), including exosomes, prove to have great potential when it comes to diagnosis and targeted therapy. Due to their natural ability to pass through biological barriers, depending on their origin, EVs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 142 publications
0
58
0
Order By: Relevance
“…Because exosomes are relatively conservative in structure and play an important role in transmitting information from primitive cells to recipient cells, more and more studies have focused on the application of exosomes as therapeutic agents, drug delivery vehicles, and diagnostic targets (Lorenc et al, 2020). Studies have confirmed that the specific metastasis and enrichment of exosomes have an important impact on cancer progression (Mo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Because exosomes are relatively conservative in structure and play an important role in transmitting information from primitive cells to recipient cells, more and more studies have focused on the application of exosomes as therapeutic agents, drug delivery vehicles, and diagnostic targets (Lorenc et al, 2020). Studies have confirmed that the specific metastasis and enrichment of exosomes have an important impact on cancer progression (Mo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes, the smallest form of EVs, with diameters ranging from 30-150 nm [78], are usually synthesized through an endosomal-sorting complex required for transport (ESCRT)dependent or ESCRT-independent pathways [79][80][81][82]. The ESCRT-dependent pathway for exosome biogenesis usually involves a series of budding processes that are facilitated by complex protein machinery, which is primarily made up of four distinct ESCRT proteins (0 to III).…”
Section: Biogenesismentioning
confidence: 99%
“…After further interacting with ESCRTs I/II and forming a total complex with ESCRT III, plasma membrane infolding begins, resulting in the formation of a cup-shaped early endosome that contains cell-surface proteins and soluble bioactive substances that are accumulated from the extracellular environment. As this early endosome buds inward, it matures into a late endosome that subsequently undergoes a secondary endosomal membrane invagination to form a multivesicular body containing intraluminal vesicles [80,[83][84][85][86]. These intraluminal vesicles have similar membrane positioning to the cell surface, where extracellular domains of transmembrane protein face the extracellular environment while enclosing the cytosolic entities [87].…”
Section: Biogenesismentioning
confidence: 99%
“…Based on tumor type or specific disease features, MVs could be engineered with crystalline ion or non-ion markers to obtain highly biocompatible targeted contrast agents [ 97 , 98 ]. Currently, superparamagnetic iron oxide nanoparticles (SPIOn), ultrasmall superparamagnetic iron oxide nanoparticles (USPIOn), and gadolinium represent the best diagnostic tools for the MRI detection of marked EVs [ 97 , 98 ]. Alternatively, gold rearranged EVs constitute the equivalent media in CT [ 99 , 100 ].…”
Section: Evs Targeted Contrast Media In Current Imagingmentioning
confidence: 99%